2010
DOI: 10.1210/jc.2010-1571
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Alendronate Dose and the Long-Term Absolute Risk of Subtrochanteric and Diaphyseal Femur Fractures: A Register-Based National Cohort Analysis

Abstract: Alendronate-treated patients are at higher risk of hip and subtrochanteric/diaphyseal fracture than matched control subjects. However, large cumulative doses of alendronate were not associated with a greater absolute risk of subtrochanteric/diaphyseal fractures than small cumulative doses, suggesting that these fractures could be due to osteoporosis rather than to alendronate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
87
1
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 16 publications
4
87
1
5
Order By: Relevance
“…(12) Duration of exposure was considered in a cohort study from Denmark, where the rates of all subtrochanteric and diaphyseal fractures were 13 per 10,000 untreated women and 31 per 10,000 women who were using bisphosphonates, with similar rates in those with short-or long-term exposure. (13) In contrast, a Canadian study of elderly women who were hospitalized with a diaphyseal femur fracture found an increased risk in those treated with more than 5 years of bisphosphonates. (14) A serious limitation of these studies is the reliance upon International Classification of Diseases, Ninth Revision (ICD-9) codes only to identify the cases.…”
Section: Introductionmentioning
confidence: 95%
“…(12) Duration of exposure was considered in a cohort study from Denmark, where the rates of all subtrochanteric and diaphyseal fractures were 13 per 10,000 untreated women and 31 per 10,000 women who were using bisphosphonates, with similar rates in those with short-or long-term exposure. (13) In contrast, a Canadian study of elderly women who were hospitalized with a diaphyseal femur fracture found an increased risk in those treated with more than 5 years of bisphosphonates. (14) A serious limitation of these studies is the reliance upon International Classification of Diseases, Ninth Revision (ICD-9) codes only to identify the cases.…”
Section: Introductionmentioning
confidence: 95%
“…(1)(2)(3)(4)(5)(6)(7)(8) However, the increased risk of ST/FS fractures in patients taking bisphosphonates long term has not been clearly established and might be related to fragility fractures. (9)(10)(11)(12) Although the incidence of hip fractures has been well characterized, the incidence of ST/FS fractures has only recently been reported. A few epidemiology studies have looked at the prevalence of femoral fractures, and pointed out that their occurrence in elderly women might result from bone fragility.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies with long-term drug-dispensing information exist, they have had to rely on diagnosis codes, so atypical femur fractures could not be distinguished from other subtrochanteric or diaphyseal femur fractures. (1,2) The former type of study may show correct incidence rates yet provide odds ratios (OR) that are too high because of the undercapture of past drug exposure, whereas the latter type of study will provide incidence rates that are too high and odds ratios that are too low because they include fractures that may not be atypical.…”
mentioning
confidence: 99%